Ricochet Dance Company Review - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2001)
PALABRAS CLAVE: Ricochet Dance Company, Karin Fisher-Potisk, Kate Gowar, House of Magnet.
Dentro del apartado "Dance Now. Flying High. Dance Umbrella 2001".